POTENCIALIDADES E DIRETRIZES BÁSICAS DE MODELAGEM BIM VISANDO ATENDER AS ESPECIFICAÇÕES DE DESEMPENHO DE EDIFICAÇÕES - Soliman Junior, João; Lorenzi, Luciani Somensi; Formoso, Carlos Torres (ENCONTRO NACIONAL DE TECNOLOGIA DO AMBIENTE CONSTRUÍDO, 2018)
Building performance has been a recurrent subject regarding the development and evaluation of building designs. The use of Building Information Modelling (BIM) within the architecture and construction backgrounds has demonstrated to be an effective way of dealing with great amounts of information during design phase. Despite the possibility of developing virtual models with almost all relevant information for design, construction and operation, the input of building performance data in the models still remains a challenge. This is because information within these models should be addressed according to the way it should be verified later on. This paper explores how information can be inserted in building models using BIM-based tools, according to the NBR 15.575:2013 demands. The main contribution of this work is a set of guidelines which support the development of building models focused on building performance. We have encountered discrepancies related to the way data can be addressed within the models and how regulations demand information to be analysed.